Motivasi dan Perilaku Konsumen dalam Keputusan Pembelian Produk Kerajinan Kulit di Yogyakarta - Eny Sulistyowati (Jurnal Maksipreneur, 2014)
Success in carrying out business activities can not be separated from the marketing concept of customer satisfaction or customer priority. Likewise, the leather industry in Yogyakarta. To achieve business success, must be able to understand what motivates consumers to buy their products, including also understand consumer behavior. The decision will purchase a product by the consumer is influenced by various factors, both internal and external factors. Factors include cultural factors, social factors, Personal factors, psychological factors which include motvasi, perception, knowledge, beliefs, and attitudes. Determine the factors that are considered by consumers to buy the product, then the manufacturer will be able to determine the right strategy in improving business.